2020
DOI: 10.21203/rs.3.rs-38254/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effect of High-fat Diet and Exercise on KISS-1/GPR54 Expression in Testis of Growing Rats

Abstract: Purpose: To find the expression of KISS-1 and GPR54 in rats testis from PND 21st to 56th. Method: 128 three-week-old weaned rats underwent high-fat diet and exercise (60%–70% VO2max, 1 h/day, 5 days/week) intervention and were randomly divided into group C, CE, HC, or HE. Sample time points were set on the PND 21st, 35th, 43rd, and 56th. The testicular testosterone and the mRNA content, and protein content of KISS-1 and GPR54 in testis tissue were detected by ELISA, RT-qPCR, and Western blotting. Result: (1) T… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
(12 reference statements)
1
1
0
Order By: Relevance
“…The work of Ullah et al in male mouse supports our present nding that high-fat-diet could induced precocious puberty even in normal body weight mouse [1]. Furthermore, we show that although the expression of Kiss-1 increased after high-fat diet intervention, it still maintained the change trend during the development process of male rats, which increased rst and then decreased, and peak at 43D, and the GSI curve also do not change during development [14]. We demonstrate that testes weight and GSI did not show any change after high-fat diet, but serum testosterone levels and testicular morphology was affected.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The work of Ullah et al in male mouse supports our present nding that high-fat-diet could induced precocious puberty even in normal body weight mouse [1]. Furthermore, we show that although the expression of Kiss-1 increased after high-fat diet intervention, it still maintained the change trend during the development process of male rats, which increased rst and then decreased, and peak at 43D, and the GSI curve also do not change during development [14]. We demonstrate that testes weight and GSI did not show any change after high-fat diet, but serum testosterone levels and testicular morphology was affected.…”
Section: Discussionsupporting
confidence: 90%
“…Kiss-1, GPR54 and their downstream factors PLC increased continuously from PND 21 and reached a peak at PND 43, and they had decreased measurably at PND 56. In our previous studies on high-fat diet and exercise on testis of growing male rats, the GSI which symbolizes the reproductive development of rats also showed this trend [14], we suggested that the expression of Kiss-1 in hypothalamic was closely related to reproductive function. Takumi et al measured the relative expression of Kiss-1 in the hypothalamic of rats at 3, 4, 5, 6, and 8 weeks old, and found that Kiss-1 expression increased gradually from three to ve weeks old, and then decreased obviously at eight weeks old, especially in female rats [15].…”
Section: Discussionmentioning
confidence: 59%